Религия и молодежь: ключевые факторы взаимодействия - Емельянова, М.Ю. (Культура народов Причерноморья, 2014)
В статье анализируются факторы положительного влияния религии на молодежь, среди
которых особое внимание уделяется нравственной системе.
В статье приведены результаты исследований зарубежных авторов, которые теоретически
демонстрируют, каким образом религиозная вера помогает формированию достойного молодого
поколения. Религиозное влияние рассматривается с социологической точки зрения, так как именно в
таком аспекте возможно проследить воздействие религиозной веры на молодое поколение. У статті аналізуються фактори позитивного впливу релігії на молодь, серед яких особлива
увага приділяється моральній системі .
В роботі наведені результати досліджень закордонних авторів, які теоретично демонструють, яким
чином релігійна віра допомагає формуванню гідного молодого покоління. Релігійний вплив розглядається
з соціологічної точки зору, тому що саме в цьому аспекті можливо простежити вплив релігійної віри
на молоде покоління. A great number of studies show that religion is a factor promoting positive and healthy influence on
the lives of young people. Although existing theoretical studies and explanations for these religious effects
remain largely fragmented and not systematized. The article attempts to formulate a more systematic, integrated,
and coherent account of religion's constructive influence in the lives of youth, suggesting nine key factors based
on the research of Christian Smith (moral directives, spiritual experiences, role models, community and
leadership skills, coping skills, cultural capital, social capital, network closure, and extra-community links) that
are grouped in three key dimensions of influence (moral order, learned competencies, and social and
organizational ties). The article gives the factors of positive religious influence, among which special attention is
paid to moral system that takes the first place among all nine factors in three groups. Results of search reported
in the article demonstrate how religious belief helps to grow up decent young generation. The word «decent»
means that young people behave according to certain norms adopted in the society. And these norms are
understood in general sense and in the context of culture. Religious influence is viewed from the sociological
point of view which helps to trace certain results of influence of religious belief on young generation